Memaksimalkan Pembelajaran Gerak Menggunakan Bola Pada Siswa Sekolah Dasar - Febby Syafita Putri; Rahma Dewi (Journal Physical Health Recreation (JPHR), 2022)
Sports using balls are very popular with people who can provide pleasure and also train gross motor skills in children. However, some children, especially those in elementary school, are still afraid to use a ball. This is a problem that needs to be addressed, because the ball is the most popular game for children today. Physical education teachers need to find ways to help children not be afraid to play ball.